2020
DOI: 10.1016/j.jcot.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pathological fracture of the femur in Alagille Syndrome: A case report

Abstract: Alagille Syndrome is a rare autosomal dominant genetic disorder, occur only 1:70,000 in population, and characterized by reduced interlobular bile ducts, and resultant nutritional deficiencies associated with the inability to absorb fat-soluble vitamins such as vitamin D. Patients are at risk for secondary osteoporosis, rickets/osteomalacia, and ultimately may result in fracture. The majority of patients suffer from chronic cholestasis, which can have a variety of adverse effects on bone metabolism. Hypothyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the study by [6] the incidence of cubitus deformity was reported varus reached 26.1%. Approximately 25% of patients treated with open reduction surgery experience a varus deformity which is thought to be caused by inadequate reduction [7]. Type III supracondylar fractures of the humerus are generally treated with operative measures with closed reduction or open reduction techniques accompanied by percutaneous pinning in medial, lateral or cross positions.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by [6] the incidence of cubitus deformity was reported varus reached 26.1%. Approximately 25% of patients treated with open reduction surgery experience a varus deformity which is thought to be caused by inadequate reduction [7]. Type III supracondylar fractures of the humerus are generally treated with operative measures with closed reduction or open reduction techniques accompanied by percutaneous pinning in medial, lateral or cross positions.…”
Section: Introductionmentioning
confidence: 99%